Fulminant Mucormycosis Involving Paranasal Sinuses: A Rare Case Report - Komali Garlapati; Sunanda Chavva; Rahul Marshal Vaddeswarupu; Jyotsna Surampudi (Case Reports in Dentistry)
Mucormycosis is an opportunistic fulminant fungal infection, which has the ability to cause significant morbidity and frequently mortality in the susceptible patient. Common predisposing factors include diabetes mellitus and immunosuppression. The infection begins in the nose and paranasal sinuses due to inhalation of fungal spores. The fungus invades the arteries leading to thrombosis that subsequently causes necrosis of the tissue. The infection can spread to orbital and intracranial structures either by direct invasion or through the blood vessels. Here we describe a case of mucormycosis of maxillary antrum extending to ethmoidal and frontal sinus and also causing necrosis of left maxilla in an uncontrolled diabetic individual to emphasize early diagnosis and treatment of this fatal fungal infection.